A Study on Students’ Ability in Literal and Inferential Comprehension of English Texts - Sarah Kamagi (AIBPM Publisher, 2020)
Comprehension is of at least two different types, literal and inferential comprehension. Literal comprehension is roughly defined as the understanding of messages and are explicitly stated in the text being read. Inferential comprehension is roughly defined as the understanding of messages implicitly started in the text being read, or messages which are not stated but implied. Inference is a process by which readers use hints to gather information. In making inferences, we go beyond surface details and read between the lines to reach information logically. Factual details in what we read provide the basis of our knowledge. But not every bit of information is easily apparent or clearly stated. Hints or suggestions may appear that you have to build upon with your own knowledge and experience in order to understand something fully. because information is not always stated in exact terms, we must supply our own information from details or ideas that are only suggested by the writer. we can’t always be certain that what we supply is absolutely right. but if we follow hunches that are based on evidence, we can be fairly sure about some things, even if they are only hinted at. Literal comprehension is considered easier than that of inferential comprehension. It is easier do to the fact that since the message is explicitly stated, is does not require longer time and much effort to decode it (Weber, 1980).